1985
DOI: 10.1200/jco.1985.3.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin's lymphoma of the stomach: a prospective pilot study of surgery plus chemotherapy in early and advanced disease.

Abstract: A prospective pilot study of 23 patients with non-Hodgkin's lymphoma involving the stomach was undertaken to assess the efficacy of surgical resection followed by chemotherapy with adjuvant cyclical cyclophosphamide, vincristine, and prednisolone (CVP) in early stage disease, and cyclical cyclophosphamide, vincristine, prednisolone, and doxorubicin (CHOP) in advanced disease. One of 18 evaluable patients died postoperatively; 17 of 18 completed therapy and are alive and disease-free at a median follow-up of 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
6

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 18 publications
1
20
0
6
Order By: Relevance
“…Probably, the better prognosis of resected patients depends not only on the presence of a smaller post-operative tumour mass, but also on the lower rate of gastrointestinal perforation or haemorrhage, which are rather frequent complications of non-resected lymphomas (Hande et al, 1978;Fleming et al, 1982;Weingrad et al, 1982;Liang et al, 1987;Naqvi et al, 1969). We had no such complication during chemotherapy, in keeping with several previous reports using a chemotherapeutic treatment (Paulson et al, 1983;Sheridan et al, 1985;Liang et al, 1987;Janus et al, 1984).…”
Section: Complicationssupporting
confidence: 62%
See 3 more Smart Citations
“…Probably, the better prognosis of resected patients depends not only on the presence of a smaller post-operative tumour mass, but also on the lower rate of gastrointestinal perforation or haemorrhage, which are rather frequent complications of non-resected lymphomas (Hande et al, 1978;Fleming et al, 1982;Weingrad et al, 1982;Liang et al, 1987;Naqvi et al, 1969). We had no such complication during chemotherapy, in keeping with several previous reports using a chemotherapeutic treatment (Paulson et al, 1983;Sheridan et al, 1985;Liang et al, 1987;Janus et al, 1984).…”
Section: Complicationssupporting
confidence: 62%
“…This relapse rate seems to be lower in patients treated with chemotherapy (Paulson et al, 1983;Economopoulos et al, 1985;Sheridan et al, 1985;Janus et al, 1984;Shepherd et al, 1988). Hence, our findings (e.g.…”
Section: Complicationsmentioning
confidence: 62%
See 2 more Smart Citations
“…Favourable results for stage I and II PGL using surgical resection followed by chemotherapy have been reported by several authors (Paulson et al, 1983;Sheridan et al, 1985;Shepherd et al, 1988;Bellesi et al, 1989;Pasini et al, 1994), but these reports failed to discriminate between stage I and stage II disease. In the present study, we focused on stage II PGL because the results obtained from a previous study (Takenaka et al, 1981) suggested that: (a) stage I PGL is cured by gastrectomy alone; and (b) stage II PGL relapses occasionally without adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%